2018
DOI: 10.1111/sms.13249
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the best body‐weight‐status index associated with metabolic risk in youth

Abstract: This study investigated the association of six different anthropometric markers with metabolic syndrome to find the most suited to predict children at risk. Sample comprises 1324 Portuguese youth (701 girls, 623 boys), aged 10-17 years. Six anthropometric markers were included: body mass index (BMI), BMI z-score, tri-ponderal index (TPI), waist circumference (WC), WC/height ratio (WC/H), and WC/H adjusted ratio (WC/H ). A standardized metabolic risk score (zMR) was computed by summing of standardized values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 40 publications
(95 reference statements)
1
25
0
Order By: Relevance
“…With regard to the relationship between BMI and cardiometabolic risk factors, a series of studies were conducted in the past few decades. BMI and BMI SDS have also been demonstrated to be significantly relevant anthropometric markers to predict metabolic risk in youth 2123 . However, few studies have been conducted regarding the association of TMI with cardiometabolic risk factors 10 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relationship between BMI and cardiometabolic risk factors, a series of studies were conducted in the past few decades. BMI and BMI SDS have also been demonstrated to be significantly relevant anthropometric markers to predict metabolic risk in youth 2123 . However, few studies have been conducted regarding the association of TMI with cardiometabolic risk factors 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the sample, there were a small number of 16 and 17‐year‐old children. These were combined into the 15‐year‐old group, ie, 15+; for analysis, see Gomes et al Sample 3 consisted of 1745 children (859 boys) aged 7 to 17 years old, recruited as part of the Active Vouzela project in the midlands of Portugal (see Chaves et al). Sample 4 consisted of 2365 children (1197 boys) aged 8 to 17 years old, recruited as part of the Portuguese sibling study on growth, fitness, lifestyle, and health (see Pereira et al).…”
Section: Methodsmentioning
confidence: 99%
“…Studies from many countries validated that a universal WHtR≥0.5 is a better predictor of metabolic disorder risk in adolescents, independent of sex or age [8]. Another study suggested showed that compared with BMI z score and WC, the WHtR was the worst at predicting metabolic risk in adolescents [9]. Kim et al [3] reported a WHtR cutoff point of 0.48 for abdominal obesity with metabolic disorder in 13- to 18-year-old Korean adolescents based on the Korea National Health and Nutrition Examination Survey (2005–2015) data.…”
mentioning
confidence: 99%